MRI tracking of autologous pancreatic progenitor-derived insulin-producing cells in monkeys - Zou, Chunlin (Sci Rep, 2017)
Insulin-producing cells (IPCs) derived from a patient’s own stem cells offer great potential for autologous transplantation in diabetic patients. However, the limited survival of engrafted cells remains a bottleneck in the application of this strategy. The present study aimed to investigate whether nanoparticle-based magnetic resonance (MR) tracking can be used to detect the loss of grafted stem cell-derived IPCs in a sensitive and timely manner in a diabetic monkey model. Pancreatic progenitor cells (PPCs) were isolated from diabetic monkeys and labeled with superparamagnetic iron oxide nanoparticles (SPIONs). The SPION-labeled cells presented as hypointense signals on MR imaging (MRI). The labeling procedure did not affect the viability or IPC differentiation of PPCs. Importantly, the total area of the hypointense signal caused by SPION-labeled IPCs on liver MRI decreased before the decline in C-peptide levels after autotransplantation. Histological analysis revealed no detectable immune response to the grafts and many surviving insulin- and Prussian blue-positive cell clusters on liver sections at one year post-transplantation. Collectively, this study demonstrates that SPIO nanoparticles can be used to label stem cells for noninvasive, sensitive, longitudinal monitoring of stem cell-derived IPCs in large animal models using a conventional MR imager.